Topics in theoretical Asian linguistics studies in honor of John B. Whitman - Nishiyama, Kunio; Kishimoto, Hideki; Aldridge, Edith; Whitman, John, 1954- (Linguistik aktuell/Linguistics today (LA),, 2018)
"Dedicated to John B. Whitman, this collection of seventeen articles provides a forum for cutting-edge theoretical research on a wide range of linguistic phenomena in a wide variety of Asian languages, including Japanese, Korean, Chinese, Austronesian, Indo-Aryan, and Thai. Ranging from syntax and morphology to semantics, acquisition, processing and phonology, from synchronic and/or diachronic perspectives, this collection reflects the breadth of the honoree's research interests, which span multiple research subfields in numerous Asian languages"--